Administration of the nicotinic acetylcholine receptor agonists ABT-089 and ABT-107 attenuates the reinstatement of nicotine-seeking behavior in rats - Lee, Alycia M. (2014)
Current smoking cessation pharmacotherapies have modest efficacy, and most smokers relapse within the first few days after a quit attempt. Nicotine withdrawal-induced craving and cognitive impairments predict smoking relapse during abstinence and suggest that cognitive-enhancing drugs may prevent relapse. ABT-089 and ABT-107 are subtype-selective nAChR agonists that improve cognitive performance in laboratory animals. However, there are no studies examining the effects of ABT-089 and ABT-107 on nicotine self-administration and the reinstatement of nicotine-seeking behavior, an animal model of relapse in human smokers. The goal of the present study was to determine the effects of the α4β2*/α6β2* nAChR agonist ABT-089 and the α7 nAChR agonist ABT-107 on nicotine taking and seeking in rats. The effects of acute ABT-089 and ABT-107 pretreatment on nicotine self-administration and reinstatement were tested in male Sprague Dawley rats. Parallel studies of ABT-089 and ABT-107 on sucrose self-administration and reinstatement were tested in separate groups of rats to determine if the effects of these drug treatments generalized to other reinforced behaviors. Nicotine and sucrose self-administration behaviors were not altered following acute administration of ABT-089 (0, 0.12, 1.2 and 12.0 mg/kg) or ABT-107 (0, 0.03 and 0.3 mg/kg). In contrast, both ABT-089 and ABT-107 pretreatment dose-dependently attenuated nicotine reinstatement. These effects were reinforcer-specific as no effects of ABT-089 or ABT-107 pretreatment on sucrose seeking were noted. Taken together, these findings suggest that ABT-089 and ABT-107 do not affect nicotine consumption, but may reduce the likelihood that a smoking lapse will lead to relapse.